(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
It has studied involves the investigation of the spectrum, linear, and nonlinear optical M), doped with polymer and -5 characteristics of (Orcein) organic laser dye at condensations (10 nanomaterials, to apply it in the field of nonlinear optical properties. It is possible to improve and enhance many of the characteristics of organic dyes by performing them with polymer and nanoparticle substances, that is advantageous for practical applications. The spectral optical properties for all prepared samples have been studied using a spectrophotometer for all prepared samples. The measured nonlinear is involved utilizing (Z - Scan) method in two cases (Open aperture) and (Close aperture) to get nonlinear refractile index (n2) and nonlinear absorption factor (β). A (457nm) wavelength solid-state laser was used to conduct the experiments. The findings revealed that increasing the nonlinear refractive index caused the nonlinear absorption coefficient to decrease, but that raising the nonlinear refractive index caused the nonlinear absorption coefficient to increase for all of the produced samples. The nonlinear characteristics of the doped samples with the polymer were found to be improved, and the nonlinear refractive index of all samples increased as the power of the laser was increased. The nonlinear absorption coefficient of all samples, on the other hand, falls as the power of the sample increases.